Association of early versus delayed normalisation of left ventricular ejection fraction with mortality in ischemic cardiomyopathy. Issue 1 (15th March 2021) - Schiffer, Walter B; Perry, Andrew; Deych, Elena; Brown, David L; Adamo, Luigi
Abstract : Objective: In patients with non-ischaemic cardiomyopathy and reduced left ventricular ejection fraction (LVEF), normalisation of LVEF is associated with improved outcomes. However, data on patients with ischaemic cardiomyopathy and recovered LVEF are lacking. The goal of this study was to assess the prognostic significance of normalisation of the LVEF in patients with ischaemic cardiomyopathy. Methods/Results: We performed a non-prespecified post hoc analysis of the Surgical Treatment for Ischaemic Heart Failure (STICH) trial to determine the association between normalisation of LVEF (>50%) and mortality during follow-up. Of the 1212 patients with LVEF <35% enroled in the STICH trial, 932 underwent assessment of LVEF at 4 months and/or 2 years after enrolment. Among them, 18 patients experienced normalisation in LVEF at 4-month follow-up and 35 patients experienced recovery in LVEF at 2 years. Recovery of LVEF at 4 months and recovery of LVEF at 2 years were not correlated. Recovery of LVEF at 4 months was not associated with reduced all-cause mortality in unadjusted analysis (log-rank test p=0.54) or in Cox proportional hazards analysis (HR: 0.93; 95% CI: 0.48 to 1.80; p=0.82). Ejection fraction recovery at 2 years was associated with a reduction in all-cause mortality, both in unadjusted analysis (log-rank test p=0.004) and in the Cox proportional hazard model (HR: 0.41; 95% CI: 0.21 to 0.80; p=0.009). Conclusions: In patients with ischaemic cardiomyopathy, delayed normalisation of LVEF is associated with reduced mortality, whereas early recovery of LVEF is not. Further studies are needed to confirm these findings.